### Home > CC4 > Chapter 11 > Lesson 11.2.6 > Problem 11-133

11-133.

Solve the following equations as indicated. Check your solutions if possible. Homework Help ✎

Solve for

*x*: 0 =Solve for

*x*:*x*^{2}− 3(2*x*+ 3) =*x*^{2}− 3Solve for

*p*: 0 = (*p*− 3)^{2}−*p*^{2}Solve for

*w*:*u*=

*x* = 1

Subtract *x*^{2} from both sides of the equation. Be careful to distribute a −3 over the quantity in parentheses.

(*p* − 3)^{2} = (*p* − 3)(*p* − 3)

Multiply both sides of the equation by *w* then divide both sides by *u*.